1976
DOI: 10.1149/1.2132920
|View full text |Cite
|
Sign up to set email alerts
|

Burning and Extinction of a Laser‐Ignited Carbon Particle in Quiescent Mixtures of Oxygen and Nitrogen

Abstract: Experimental data on the burning mode and lifetime, on the surface temperature, and on the spontaneous extinction of a laser‐ignited particle of electrode carbon (50–200μ) in quiescent mixtures of oxygen and nitrogen at room temperature are presented. The test variables were the oxygen mass fraction (0.5–1) and the pressure (0.5–3 atm) of the mixture. High speed cinemicrography of the burning particle showed that the visible combustion zone was restricted to the surface. Two theoretical models, one neglecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 14 publications
6
13
0
1
Order By: Relevance
“…Even combustion in ignited regime was found to undergo extinction near the end as the specific surface area of the coal char decreased drastically. This was in line with experimental observations of Ubhayakar and Williams [41]. The burnout time was found to attain a minima with respect to the particle radius due to shift in combustion regime from extinction to ignition, which was in conformity with the observations of Sundaresan and Amundson [21] for combustion of carbon particles.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Even combustion in ignited regime was found to undergo extinction near the end as the specific surface area of the coal char decreased drastically. This was in line with experimental observations of Ubhayakar and Williams [41]. The burnout time was found to attain a minima with respect to the particle radius due to shift in combustion regime from extinction to ignition, which was in conformity with the observations of Sundaresan and Amundson [21] for combustion of carbon particles.…”
Section: Resultssupporting
confidence: 91%
“…10). Similar ignition in the combustion regime and extinction near the end were observed experimentally by Ubhayakar and Williams [41].…”
Section: Simulation Study Of Coal Char Samplessupporting
confidence: 86%
“…The time dependent equ1tion (3) can therefore be written as (9) The term H1 is the heat gain from absmption of the laser energy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, under an assumption of quasi-steadiness in the gas phase, formulation has been conducted, as described in the previous works [34][35][36][37][38][39], so that only the final solution is presented herein, with adhering almost completely to the model definition, formulation, and nomenclature of Refs. [41,42].…”
Section: Critical Particle Sizementioning
confidence: 99%
“…Unfortunately, however, it has been rare for those results to be compared with theoretical results, in spite of the fact that such formulations [34][35][36][37][38] for a spherical particle have widely been introduced in many textbooks. Furthermore, it has even been suggested that small particles may be considered to burn under quiescent condition [39].…”
Section: Introductionmentioning
confidence: 99%